The Evaluation of the Epidemiology and Etiology of Plate and Screw Removal after Orthognathic Surgery in Mashhad Dental School during 2016-2018 - Reza Shahakbari; Sahand Samiee rad; Shilan Hasanalizade; Abdollah Javan Rashid (Mashhad University of Medical Sciences, 2020)
Introduction: The present study aimed to evaluate the rate ofminiplate and miniscrew removal and its etiology after orthognathic surgery during 2016-2018. Materials & Methods: For the purposes of this cross-sectional study, all the patients who referred to the surgical department of Dental School of Mashhad University of Medical Sciences, for orthognathic surgery were included. All cases were assessed to determine whether the miniplate and miniscrew were removed after the surgery or not. Subsequently, the age, gender, cause of removal, and type of their orthognathic surgery were identified. Finally, the collected data were analyzed in SPSS software (version 21). Results: The present study was performed on 69 subjects with the average age of 24.9±4.09 who underwent orthognathic surgery during 2016-2018. The aim was to analyze the miniplate and miniscrew removal and related variables. Based on the results, the rate of miniplate and miniscrew removal was 10.14% (7 cases out of 69 patients). It was found that infection and plate exposure were the most common reasons for miniplate and miniscrew removal after orthognathic surgery. Moreover, miniplate and miniscrew removal was more frequent in the mandible, compared to the maxilla. Furthermore, the removal had a significant relationship with the type of jaw movement and usage of alcoholic drinks (P<0.05). Conclusion: Regarding the low rate of miniplate removal after orthognathic surgery (10.14%), it can be concluded that there is no need to remove asymptomatic titanium miniplates. It is only necessary to do so when there are indications and clear symptoms for the removal.